Grit pada mahasiswa: Dapatkah diturunkan menggunakan intervensi growth mindset? Grit in college students: Can it be reduced using growth mindset intervention? - Nurdin, Nur Siti Maghfira Maulani; Dewi, Eva Meizara Puspita (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
Students in facing the demands of lectures can experience difficulties and experience failure, so grit is needed. Students with low grit tend to change interests easily and think about changing majors because they feel they have not succeeded in getting the right thing. Increasing grit can be done by developing a growth mindset in individuals. This research aims to test the effectiveness of growth mindset intervention in increasing grit in students. The participants in this research were 17 Makassar State University students divided into two groups (9 participants in the experimental group and 8 participants in the control group). Participants were determined through a purposive sampling technique. The research design used in this study was a randomized pretest-posttest control group design. Data collection was carried out using the grit scale (∝ = 0.716). The data analysis techniques used are the Wilcoxon test and the Mann-Whitney test. Experimental group participants were proven to experience an increase in grit scores after receiving a growth mindset intervention for two weeks. The findings of this research can make growth mindset intervention a way to increase student grit.